2015
DOI: 10.1007/s12098-014-1660-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pediatric Epilepsy Surgery

Abstract: Epilepsy surgery has become an accepted treatment for drug resistant epilepsy in infants and children. It has gained ground in India over the last decade. Certain epilepsy surgically remediable syndromes have been delineated and should be offered surgery earlier rather than later, especially if cognitive/behavioral development is being compromised. Advances in imaging, particularly in MRI has helped identify surgical candidates. Pre-surgical evaluation includes clinical assessment, structural and functional im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…[4][5][6] Of newly diagnosed patients with epilepsy, nearly half (i.e., 47%) will attain seizure freedom with just one AED. 7 Another 13% of patients are estimated to achieve seizure freedom with the addition of a second medication. Beyond this, an effect of diminishing returns is established, with only 4% benefiting from the addition of a third agent.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Of newly diagnosed patients with epilepsy, nearly half (i.e., 47%) will attain seizure freedom with just one AED. 7 Another 13% of patients are estimated to achieve seizure freedom with the addition of a second medication. Beyond this, an effect of diminishing returns is established, with only 4% benefiting from the addition of a third agent.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, CC is being increasingly replaced with vagal nerve stimulation, [21][22][23][24][25][26][27] mostly because the former is considered as a palliative "destructive" surgery. More recent studies have demonstrated that after CC, in some patients, there is a better localization of the epileptogenic focus.…”
mentioning
confidence: 99%
“…I have outlined the present status of epilepsy surgery in children [6]. We at the Hinduja Hospital in Mumbai have a small experience since the last several years in evaluation and surgical treatment of children with refractory epilepsies.…”
mentioning
confidence: 99%